How agricultural technological innovation influences carbon emissions: insights from China - Tang, Fengxia; Tan, Juntao; Qiu, Fangdao; Gu, Shulin (Frontiers in Sustainable Food Systems, 2025)
Under the context of global warming, the continuous rise in greenhouse gas emissions has become a critical concern. As a significant source of greenhouse gas emissions, the carbon emissions from agriculture exert a considerable impact on climate change, which cannot be overlooked. Agricultural technological innovation is crucial for reducing carbon emissions. Examining how the scale and structure of agricultural technological innovation impact agricultural carbon emissions is important for achieving the Carbon Peaking and Carbon Neutrality Goals. This research is based on data from 30 provinces in China over the period of 2013–2022. It utilizes fixed-effects models, moderation models, and spatial econometric models to empirically investigate the impact mechanisms of the scale and diversity of agricultural technological innovation on agricultural carbon emissions. The research findings reveal that: (1) China's agricultural carbon emissions exhibit an overall declining trend, while the scale of agricultural technological innovation and the level of technological diversity demonstrate a general upward trend. However, regional disparities exist. The total agricultural carbon emissions in the central regions remain relatively high, whereas the scale of agricultural technological innovation and the level of diversity decrease progressively from the southeastern coastal areas toward the inland regions. (2) The scale of agricultural technological innovation and the diversity of technologies have a significant inhibitory effect on agricultural carbon emissions. (3) Mechanism analysis reveals that the scale of agricultural technological innovation positively moderates the impact of technological diversity on agricultural carbon emissions. Specifically, an increase in the scale of technological innovation enhances the inhibitory effect of diversity on carbon emissions. (4) Spatial effect analysis indicates that there is a significant spatial correlation between the scale and diversity of agricultural technological innovation. The scale of agricultural technological innovation has a negative spatial spillover effect on agricultural carbon emissions in adjacent areas. The increase in the scale of local technological innovation helps to spread agricultural technological resources to neighboring areas and reduce their agricultural carbon emissions. This study enriches the research on the impact of agricultural technology innovation on agricultural carbon emissions, providing theoretical references for promoting agricultural technology innovation and sustainable agricultural development.